Facile in situ reductive synthesis of both nitrogen deficient and protonated g-C3N4 nanosheets for the synergistic enhancement of visible-light H2 evolution. Issue 10 (10th February 2020) - Li, Weisong; Guo, Zheng; Jiang, Litong; Zhong, Lei; Li, Guoning; Zhang, Jiajun; Fan, Kai; Gonzalez-Cortes, Sergio; Jin, Kuijuan; Xu, Chunjian; Xiao, Tiancun; Edwards, Peter P.
Abstract : Nitrogen deficient and protonated g-C3 N4 was fabricated by the conjoint protocol utilizing NH4 Cl as gas template and H3 PO2 as doping agent, leading to enhanced visible-light harvesting and charge carrier separation to achieve efficient H2 evolution. Abstract : A new strategy is reported here to synthesize both nitrogen deficient and protonated graphitic carbon nitride (g-C3 N4 ) nanosheets by the conjoint use of NH4 Cl as a dynamic gas template together with hypophosphorous acid (H3 PO2 ) as a doping agent. The NH4 Cl treatment allows for the scalable production of protonated g-C3 N4 nanosheets. With the corresponding co-addition of H3 PO2, nitrogen vacancies, accompanied by both additional protons and interstitially-doped phosphorus, are introduced into the g-C3 N4 framework, and the electronic bandgap of g-C3 N4 nanosheets as well as their optical properties and hydrogen-production performance can be precisely tuned by careful adjustment of the H3 PO2 treatment. This conjoint approach thereby results in improved visible-light absorption, enhanced charge-carrier separation and a high H2 evolution rate of 881.7 μmol h −1 achieved over the H3 PO2 doped g-C3 N4 nanosheets with a corresponding apparent quantum yield (AQY) of 40.4% (at 420 nm). We illustrate that the synergistic H3 PO2 doping modifies the layered g-C3 N4 materials by introducing nitrogen vacancies as well as protonating them, leading to significant photocatalytic H2 evolution enhancements, while the g-C3 N4 materials doped with phosphoric acid (H3 PO4 ) are simply protonated further, revealing the varied doping effects of phosphorus having different (but accessible) valence states.